Formulation and characterization of bay leaf extract nanophytosomes (Syzgium polyanthum) and affinity study of interaction with alpha glucosidase enzyme as antidiabetic - Septianti, Regina Dwi; Jafar, Garnadi; Dinayanti, Westi Nur; Dinata, Deden Indra (Institute of Computer Science (IOCS), 2025)
Introduction: Diabetes Mellitus is a metabolic syndrome disease in which around 90-95% of all cases of adults aged 20-79 years suffer from type 2 Diabetes Mellitus, with long-term conventional treatment causing side effects of hypoglycemia. Bay leaves which contain quercetin and kaempferol compounds are able to lower blood glucose levels, but have challenges in drug delivery due to easy oxidation and low bioavailability. Therefore, an innovative drug delivery system is needed, such as nanophytosomes, to increase its bioavailability. Objective: This study aims to develop a thin film formula of bay leaf extract nanophytosomes that have antidiabetic affinity with in silico studies and evaluate the physical characteristics of nanophytosomes. Method: in silico using the molecular docking method to evaluate the interaction of active compounds of bay leaves with the alpha glucosidase enzyme. Bay leaf nanophytosomes are formulated using heat homogenization and probe sonicator techniques. Characterization is carried out by measuring particle size, polydispersity index, zeta potential, and particle morphology. Results: The nanophytosome formula of bay leaf extract showed a particle size of <1000 nm, a polydispersity index of <0.5, and a zeta potential of ±25 mV. In silico studies showed that quercetin and kaempferol have a strong affinity for the α-glucosidase enzyme, which plays an important role in inhibiting glucose absorption. Conclusion: Bay leaf extract can be formulated into a phytosome-based nanoparticle delivery system that shows stable physical characteristics, high adsorption efficiency, and potential antidiabetic activity through the interaction of inhibiting the α-glucosidase enzyme.